SYNTHESIS, IN VITRO ANTIMICROBIAL ACTIVITY OF SCHIFF'S BASE, AZETIDINONES AND THIAZOLIDINONES - Mistry, Bhavnaben D.; Desai, Kishor R.; Desai, Nigam J. (International Journal of Current Pharmaceutical Research, 2016)
Objective: The objective of the present study is to synthesize 3-Chloro-4-[3-(2,4-dichloro-5-fluoro phenyl)-1H-pyrazol-4-yl]-1-(substituted) azetidin-2-one [4a-n] and 2-[3-(2,4-Dichloro-5-fluoro phenyl)-1H-pyraol-4-yl]-3-(substituted phenyl)-1,3-thiazolidin-4-one [5a-n]. The structure of all synthesized compounds were characterized by IR, 1H NMR, 13C NMR and mass spectral studies. Methods: The titled compounds 3-Chloro-4-[3-(2,4-dichloro-5-fluoro phenyl)-1H-pyrazol-4-yl]-1-(substituted) azetidin-2-one [4a-n] and 2-[3-(2,4-Dichloro-5-fluoro phenyl)-1H-pyraol-4-yl]-3-(substituted phenyl)-1,3-thiazolidin-4-one [5a-n] were synthesized by the reaction of N-{[3-(2,4-dichloro-5-fluoro phenyl)-1H-pyraol-4-yl] methylene } substituted anilin [3a-n] with chloro acetyl chloride and thioglycolic acid respectively. Compounds N-{[3-(2,4-dichloro-5-fluoro phenyl)-1H-pyraol-4-yl] methylene} substituted aniline [3a-n] were synthesized by the reaction of 3-(2,4-dichloro-5-fluoro phenyl)-1H-pyrazol-4-carbaldehyde [2] with primary aromatic amine in alcohol. All compounds were evaluated for their antimicrobial activity. Results: Compounds 3a,3b,3d,3j,3l,4d,4e,4j,4l,4m,5e,5g,5h,5n exhibited excellent to good antibacterial activity as compared to reference drugs. Conclusion: In summary, N-{[3-(2,4-dichloro-5-fluoro phenyl)-1H-pyraol-4-yl] methylene } substituted anilin [3a-n], 3-Chloro-4-[3-(2,4-dichloro-5-fluoro phenyl)-1H-pyrazol-4-yl]-1-(substituted) azetidin-2-one [4a-n] and 2-[3-(2,4-Dichloro-5-fluoro phenyl)-1H-pyraol-4-yl]-3-(substituted phenyl)-1,3-thiazolidin-4-one [5a-n] derivatives have been synthesized and characterized. In vitro antimicrobial testing of the compounds was carried out by microdilution Method. Amongst the synthesised compounds, many of them had proven their antimicrobial potency which varies from good to excellent.